Pengaruh Multiple Mikro Nutrien (MMN) Terhadap Berat Badan Bayi Baru Lahir Di Desa Pandes Klaten - Dwi Retna Prihati; Gita Kostania (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract: MMN, Newborn Baby Weight. During pregnancy food is required with good quality and quantity to meet the nutritional needs of mother and baby. The low nutritional status of pregnant women during pregnancy can lead to various adverse effects for mothers and infants, such as those born with Low Birth Weight (LBW). LBW babies have a 10 to 20 times greater chance of dying than babies born with enough birth weight. Multiple Micro Nutrient (MMN) contains 15 types of vitamins and minerals most important for pregnant women, including vitamin A, vitamin E, vitamin D, vitamin B1, vitamin B2, niacin, Vitamin B6, vitamin B12, folic acid, vitamin C, Fe , folic acid, Zink, Copper, Selenium, and Iodine. MMN is one of the nutrients to prevent the occurrence of anemia because in MMN there are factors forming Hemoglobin ie Fe, Vitamin B12 and folic acid. The availability of adequate hemoglobin makes the metabolic system work well. Lack of hemoglobin not only affects the health of the mother but also affects the health of the fetus it contains, including the growth of the fetal inhibition (such as weight, body length). The purpose of this study was to prove the effect of MMN on newborn weight in Pandes Klaten village. This type of research is arestrospective study with cross sectional design. The subjects of this study were BBL (newborn) whose mother consumed MMN during pregnancy. Different test sing Independent T-test to compare control group and treatment group. Significant value in this study was p <0.05. The results of this study were no significant difference between birth weight between control group and MMN treatment group (P = 0.879). In conclusion MMN has no significant effect on newborn weight gain.